Subtotal occlusion of the right coronary artery by Cardioband and its successful intervention via retrograde approach. Interventional flashlight. Issue 4 (April 2023) - Habedank, Dirk; Bierschenk, Sabine; Zimpel, Saskia; Huch, Jeanette; Atmowihardjo, Iskandar
Abstract: In recent years, transcatheter approaches have changed the therapy of valvular regurgitation. One of these new techniques is the Cardioband ® tricuspid valve reconstruction system (Edwards Lifesciences Corp., Irvine, CA, USA), which allows an adjustment of the ring size but may cause a temporary deformation or even occlusion of the right coronary artery (RCA) due to its close proximity. We report on a patient with symptomatic and subtotal occlusion of the RCA after Cardioband implantation. The distortion was so sharp-cornered that antegrade re-canalizations failed. Finally, the subtotal occlusion was re-opened via retrograde approach and this stent remained open in long-term follow-up. We think this complication should be known and considered when using the Cardioband system. Learning objective: Transcatheter reconstruction of the tricuspid valve by Cardioband ® can lead to subtotal occlusion of the right coronary artery, which is difficult to re-canalize.